2011
DOI: 10.1021/ja204063z
|View full text |Cite
|
Sign up to set email alerts
|

Direct Transformation of N,N-Dimethylformamide to −CN: Pd-Catalyzed Cyanation of Heteroarenes via C–H Functionalization

Abstract: This paper describes the direct cyanation of indoles and benzofurans employing N,N-dimethylformamide (DMF) as both reagent and solvent. Isotopic labeling experiments indicated that both the N and the C of the cyano group derived from DMF. This transformation offers an alternative method for preparing aryl nitriles, though it is currently limited in scope to indoles and benzofurans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
90
0
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 297 publications
(99 citation statements)
references
References 63 publications
2
90
0
4
Order By: Relevance
“…Dialkyl alkynes exhibited slightly lower reactivity than diaryl alkynes ( O-3n), which showed that the oxygen of the carbonyl group in the product originated from the initial material ( Fig. 3a) [35][36][37] . Further investigation demonstrated that 18 O could also be incorporated into benzo-fused oxindole 3n when extra 18 O-labelled water was added into the reaction system, which suggested that water might be produced and then participate in an apparent oxygen transposition in the cascade reaction (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…Dialkyl alkynes exhibited slightly lower reactivity than diaryl alkynes ( O-3n), which showed that the oxygen of the carbonyl group in the product originated from the initial material ( Fig. 3a) [35][36][37] . Further investigation demonstrated that 18 O could also be incorporated into benzo-fused oxindole 3n when extra 18 O-labelled water was added into the reaction system, which suggested that water might be produced and then participate in an apparent oxygen transposition in the cascade reaction (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…[44] Isotope-labeling experiments indicated that both the C and N of the cyano group were derived from DMF [Eqs. (10) and (11) in Scheme 26; TBA = tetra-n-butylammonium].…”
Section: Serving As a Precursor In Cyanation Reactionsmentioning
confidence: 99%
“…[43] Wie bei Changs Arbeiten [41] Jiao und Ding entwickelten eine bemerkenswerte Umsetzung, bei der DMF direkt in einen CN-Substituenten umgewandelt wird. [44] Isotopenmarkierungen zufolge stammen hierbei sowohl C als auch N der Cyangruppe aus DMF [Gl. (10) und (11) …”
Section: Dmf Als Vorstufe In Cyanierungenunclassified